Economic Valuation of Pasirpanjang Ecotourism in Lembeh Island - Mustika Permata Sari; Unstain N. W. J. Rembet; Joudy R.R. Sangari (Sam Ratulangi University, 2018)
Ecotourism is viewed as an economic incentive for the communities living near the protected areas, as well as a tool to enhance their participation to preserve an ecosystem. Pasirpanjang Ecotourism Area in Lembeh Island has been developed since some part of itsâ€™ waters were promoted as a Coastal and Small Island Conservation Area of Bitung City in 2014. The aims of this study are to estimate the economic value of Pasirpanjang Ecotourism Area using Zonal Travel Cost Method and resulting a policy recommendation to develop Pasirpanjang Ecotourism. This study was conducted in Pasirpanjang village, Sub-district of South Lembeh on May 2018. The result showed the total economic value of Pasirpanjang Ecotourism is Rp. 1,610,786,697 per annum. The result also indicated the importance of ecotourism concept to be considered by government in managing mangrove ecosystems. The potential value of the area of Pasirpanjang Ecotourism could be considered as a long term economic asset and for the sustainability of the conservation as well.Key Words: Economic Value, Pasirpanjang Ecotourism Area, Economic Incentive, Zonal Travel Cost MethodABSTRAKEkowisata dipandang sebagai insentif ekonomi bagi masyarakat yang berada di sekitar area perlindungan, serta menjadi alat untuk meningkatkan partisipasi mereka dalam upaya pelestarian suatu ekosistem. Ekowisata Pasirpanjang di Pulau Lembeh telah dikembangkan sejak wilayah perairan di sekitarnya dicadangkan sebagai Kawasan Konservasi Wilayah Pesisir dan Pulau-Pulau Kecil Kota Bitung pada tahun 2014. Penelitian ini bertujuan untuk menaksir nilai ekonomi dari Ekowisata Pasirpanjang menggunakan Metode Biaya Perjalanan Zonasi (Zonal Travel Cost Method) dan menghasilkan rekomendasi kebijakan untuk pengembangan kawasan Ekowisata Pasirpanjang. Penelitian ini dilakukan di Kelurahan Pasirpanjang di bagian selatan Pulau Lembeh pada bulan Mei 2018. Berdasarkan estimasi nilai ekonomi dari Ekowisata Pasirpanjang adalah sebesar Rp. 1.610.786.697 per tahun. Estimasi nilai tersebut menunjukan pentingnya konsep ekowisata sebagai pertimbangan oleh pemerintah dalam mengelola ekosistem mangrove. Potensi nilai Ekowisata tersebut juga dapat dipertimbangkan sebagai aset ekonomi jangka panjang dan keberlanjutan pelestarian.Â Kata kunci: Nilai ekonomi, Kawasan Ekowisata Pasirpanjang, Insentif ekonomi, Zonal Travel Cost Method